Efeitos do resfriamento cr??nio-cervical sobre a eleva????o da temperatura central e respostas psicofisiol??gicas associadas, durante dois modelos de exerc??cio realizados em ambiente quente - Silva, Renato Andr?? Sousa da (2016)
Introduction: Previous studies have found that cerebral cooling is effective to decrease the elevation in core temperature during exercises performed in hot environment. Furthermore, other have shown that the rate of increase in core temperature may vary according to the exercise mode under consideration; in contrast to self-paced exercise, controled-pace exercise requires greater muscle recruitment, thereby inducing higher increase in core temperature. The aim of this study was to examine the acute effects of cranial-cervical cooling in the rate of increase of core temperature, and physiological and psychological responses during controlled-pace and self-paced exercises performed in hot environment. Methods: Ten cyclists took part in the study, they underwent 3 preliminary sessions under ~21 ??C and 4 experimental sessions in hyperthermia (~33 ??C), that is: self-paced exercise with or without central cooling (ESP33 e ESP33C); and controlled-pace exercise with or without central cooling (ECP33 e ECP33C). In both the exercise modes they completed 20km cycling trial either in a self-paced manner anchored in ratings of perceived exertion (RPE = 16), or in a controlled-pace manner with intensity set at the mean power output recorded during preliminary self-paced exercise session under ~21 ??C. Core and peripheral temperature, cardiopulmonary and perceptive measures were obtained during exercises, while maximal voluntary muscle torque, body mass and urine density were obtained prior and post exercises. Mean responses, as well as the rate of increase in core temperature and RPE along the exercises with or without cooling were compared. Results: The control trials showed that ESP e ECP were submaximal, and affected by the elevation in environment temperature (21 ??C vs 33??C). Regarding the responses to the cranial-cervical cooling, there were cooling main effects due to reduction in exercise time, increases in power output, reduction in mean core temperature and its rate of increase. Additionally, there was lower RPE and thermal sensation. Only the oxygen uptake showed exercise mode main effects, with greater values in ECP. No exercise mode by cooling interaction effects was observed. Conclusion: The central cooling was effective to increase the motor performance, likely due to the attenuated increase in core temperature and RPE. However, the exercise mode did not determine to these responses.